Optimizing the Role of Teachers in the Learning Process with a Modern Pedagogical Approach: Bibliometric Analysis - Harry Hermawan; A Sobandi (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2024)
This research aims to understand the role of optimizing the teacher's role in developing learning in a modern pedagogy approach. The research was conducted through a systematic literature review and bibliometric analysis. Initially, an article search was carried out using the Google Scholar database in the Publish or Perish application with the keywords "optimization teacher", "learning", "pedagogy","journal". The search results obtained as many as 200 documents and then filtered them, leaving 12 articles related to keywords. After filtering, it is then processed using VOSviewer software and it can be concluded that research on the role of optimizing the teacher's role in developing learning in a modern pedagogical approach is teacher's personality still present comprehensively when they organizes and controls the learning process towards a more meaningful situation. The teacher gets more momentum for the involvement of all students in the process, where they plays a small role as a controller of learning.